Magnetizing public education: The lingering effects of magnet schools in the Cincinnati public school district, OH - Parrillo , Adam (Journal of Interdisciplinary Studies in Education, 2015)
This paper examines the racial and socioeconomic enrollment patterns resulting from magnet school programs in the Cincinnati Public School district (Ohio).  The analysis employs the measure of interracial exposure and independent t-tests to compare magnet schools with non-magnet schools across eight years, 1999-2006, and finds that there are significance differences in racial exposure and neighborhood income level of student populations.  Further, magnet school literature is reviewed in the context of the "roll-out" of market-oriented Neoliberal policy reforms where emergence of these reforms coincides with Civil Rights era desegregation, resulting in ‘voluntary choice’ of magnet schools as the court accepted and government supported policy reform.  This research is integral in broadening the discourse of contemporary school choice debates.